1984
DOI: 10.1113/expphysiol.1984.sp002805
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the Ultrastructure of the Blood‐joint Barrier in the Rabbit Knee

Abstract: SUMMARYThe ultrastructure of the barrier to water and solute exchange between blood and a synovial cavity was studied morphometrically in five rabbit knees. The synovial surface consisted of 80 % synoviocytes and 200% interstitium in direct contact with synovial fluid. The surface intercellular gaps were wide (0 1-55 ,um). A rich network of capillaries lay just beneath the surface, the commonest (modal) depth of the capillary perimeter being 5 ,sm at its nearest point. Of these capillaries, 91 % were fenestrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…(The fenestral frequency in these vessels was 2 5 per profile, which is similar to the value of 1 9 found for exocrine capillaries in the present work.) For a recent review of fenestral distribution, see Knight & Levick (1984). In this a n d~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ Fig.…”
Section: Resultsmentioning
confidence: 97%
“…(The fenestral frequency in these vessels was 2 5 per profile, which is similar to the value of 1 9 found for exocrine capillaries in the present work.) For a recent review of fenestral distribution, see Knight & Levick (1984). In this a n d~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For example, one function of the joint fluid is to provide a chemical environment for the ACL. In fact, the capillaries of the synovial membrane have been characterized as a fenestrated type, highly permeable to small hydrophilic solutes, 15,44 thus allowing nutrient diffusion. Levick 45 concluded that joint fluid absorption from the joint cavity occurs by two parallel pathways, viz.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the therapeutic outcome following IA injection is considerably lessened by drug delivery issues that include rapid clearance into the systemic circulation from the synovial ultrastructure, which offers little barrier to the diffusion of molecules in and out of a joint. 4,5 Knight and Levick 6 found that the synovial surface consists of a discontinuous layer of synoviocytes (covering 80% of the synovial lining) with wide intercellular gaps measuring 0.1-5.5 μm with no basal membrane. The IA route is even comparable to intramuscular or subcutaneous routes pharmacokinetically with regard to rapid redistribution of drug into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%